Factors Causing The Decline In Revenue Of KMP Raja Dilaut Before COVID-19 Until Pandemic Recovery - Usman, Arif Fuddin; Alimah , Andi Nur; Murtafiah, Andi; Rusnaedi; Fitriah, Rifkah (Nama Jurnal Akmi, 2023)
This research is to determine and compare KMP. Raja Dilaut income before COVID-19, during COVID-19, and the pandemic recovery period, as well as the factors causing the decline. KMP. Raja Dilaut is one of the crossing vessels owned by PT Pelayaran Nusantara Juli Rahayu which operates at the Bajoe-Kolaka Ferry Port. The purpose of this research is: 1) to determine KMP. Raja Dilaut income before, during, and during the COVID-19 recovery period, from 2018 to 2022, 2) to determine the factors causing the decline and increase in income KMP. Raja Dilaut. This research is qualitative research using interactive model data analysis techniques, starting from the data collection stage followed by data reduction, data display, and the final stage, namely the conclusion. KMP. Raja Dilaut income recap calculation results from 2018 worth "IDR 7,464.519,207", in 2019 worth "IDR 7.135.582.768", in 2020 worth "IDR 3.277.331.031", in 2021 worth "IDR 4.667.035.509", and in 2022 worth "IDR 15.948.678.745". In 2020 there was a significant decline. Ship income is only 30% of total capital costs. In 2020, at the peak of the COVID-19 pandemic, the company almost went bankrupt. The company almost closed the business because capital costs could not be covered by revenue. But the company was able to survive and survive and in 2021 revenue increased to 61% and in 2022 it rose to 70%. The most dominant causal factor in the decline in KMP Raja Dilaut income using the fishbone method includes Large-Scale Social Restrictions (PSBB), examination and mandatory Rapid Antigen testing, and the Peduli Protect application which is still difficult for the community to implement. The ship, which was originally capable of carrying 286 passengers per trip, experienced a decline of around 50-100 percent.